Photoluminescence of Er-doped YIG Crystal - Yorulmaz, S. Cigdem; Avinca, Elif; Zainullin, Farkhad; Ari, Ozan; Maksutoglu, Maksut; Khaibullin, Rustam; Rameev, Bulat Z. (Spie-Int Soc Optical Engineering, 2024)
The optical properties of erbium-doped yttrium iron garnet (Er:YIG) thin films have been studied at temperatures between 1.6 K and 260 K. Single crystal YIG thin films on GGG (Gd3Ga5O12) have been implanted with 20 keV Er+ ions to the fluences of (0.5 or 1.0) x 10(16) ion/cm(2). Erbium concentration has been kept on a level preventing a detrimental effect on the magnetic properties of the YIG garnet while providing the ion ratio enough for intense photoluminescence. Raman spectra for the YIG films on GGG substrate which are similar to the literature data have been observed. No effect of the erbium implantation on Raman peaks has been revealed and explained by the small thickness of the implanted layer. Photoluminescence signals appearing with temperature cooling between 680 nm and 720 nm have been observed and attributed to the emission from the erbium ions. Our result reveals that doping YIG by Er can be useful for tailoring the magneto-optical properties of YIG.
Conference on Quantum Information Science, Sensing, and Computation XVI -- APR 22-25, 2024 -- National Harbor, MD
Keywords: Er-implanted YIG thin films; optical spectroscopy; luminescence